The Effect of Instagram Social Media Marketing Content towards the Public Attitude through Online Engagement (Study on the National Narcotics Agency Central Kalimantan Province) - Dwi Prawitarini Soedjardjo (East Asian Journal of Multidisciplinary Research, 2023)
This research seeks to see how the public's attitude towards the infobnn_prov_kalteng social media Instagram account currently has a total of 11,500 followers, with responses in the form of comments and likes on average still below 100 for each post uploaded. The purpose of this study was to examine how much influence content marketing carried out by Central Kalimantan BNNP Public Relations on Instagram and other social media has had on public attitudes. In this study, the samples taken were followers of Instagram account infobnn_prov_kalteng, which has 266 followers. The research methodology used is quantitative and analyzed with Data Analysis Techniques: Descriptive analysis and PLS SEM analysis with Smart Pls 3.0 tools. The results of the study show that the role of online engagement is very important (76%). An important research implication is that content marketing has a positive and significant effect on public attitudes through online engagement. This has the implication that if the Central Kalimantan BNNP admin maintains the quality of the content and regularly posts by creating interesting content, the public will receive a positive response.